A study of the relative bronchodilator responsiveness in smoker asthmatics - CH., Raju; M., Ravindranath (International Journal of Advances in Medicine, 2017)
Background: Anticholinergic agents established bronchodilator agents which are in use for treatment of asthma but with slow onset and late peak of action. In contrast adrenergic agents are potent bronchodilator with fast action. Beside bronchodilatation they also improve mucociliary transport and reduce release of inflammatory mediators. Methods: After baseline spirometry at zero hour, sequential doses of salbutamol i.e. 100 micrograms were given every hour to achieve the fullest expression of a neuronal mechanism which was reflected as a plateau on dose response curve, after which the other agent, inhaled ipratropium of dose 80 micrograms was administered. This sequence was reversed on the next visit of the patient with the maximum limit of inhaled salbutamol to be 400 micrograms. Results: More number of smoker asthmatics showed eosinophil counts less than 350/cu.mm than the non-smokers. Only salbutamol showed no significant difference in smokers, while on addition of ipratropium, there was a significant change. But in the non smokers, salbutamol alone showed a marked improvement. Conclusions: For smoker asthmatics combination therapy is more useful than either agent used alone as both the sympathetic or parasympathetic tone is acting simultaneously.